A luta sindical pelo direito a um trabalho digno na agroindústria canavieira paulista como pressuposto da democracia - Ozório, Paula Cristina Monteiro (2008)
The research addresses the relationship of work in agribusiness of sugar cane in the State of São Paulo to identify the reasons and economic policies of his historic building from the first division, occupation and productive use of their lands, directed since the colonial times in its legal constructions, get to identify the legal limits of the economic power that can or not to be can showing in this relation for the identification of the State s function in a development in this process. From then will be required score the possibilities of legal and political performance of the employees, through union organization, undertake the modifications that result in effective improvement of their living conditions and work.